Beneficial Effects of Soygurt Intake in Type 2 Diabetes Mellitus in Animal Model Rat (Rattus Norvegitus) - Ni Wayan Desi Bintari; Putu Ayu Parwati (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Type 2 Diabetes Mellitus (T2DM) is the more common type of diabetes results from the ineffective use of insulin. Improvement of the metabolic system in T2DM patients can be done through the regulation of gut microbiota balance. Gut microbial improvement can be modulated directly by probiotic food consumption. Soygurt is probiotic food with a low glycemic index (GI) and glycemic load (GL) value and rich in isoflavones, which has a potential effect in reducing diabetes risk. The aim of this study is to determine the effect of soygurt consumption in blood glucose levels and body weight of albino wistar rats (Rattus norvegitus). Reseach using a completely randomized design for experimental study. Subjects of this research are 30 male rats (R. norvegistus) aged 2-3 months with average body weight 150-200 gr. Diabetic rats were induced by using single intraperitoneal injection (175 mg/kg BW) alloxan monohydrate. Soygurt feeding given once daily using oral gavage feeding. The result showed that soygurt feeding in diabetic rats with three variations of treatment could significantly (p